2021
DOI: 10.3390/su13126574
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Performance and Environmental Sustainability Indicators in Hotel Competitiveness

Abstract: Environmental protection and environmental sustainability are becoming increasingly important factors in the hotel business and their competitiveness, in a market that brings numerous benefits. Environmental sustainability is, increasingly, considered one of the most important functions of the hotel business, as well as communication and marketing, which attracts a larger number of guests. Some of the key aspects of hotel environmental sustainability are performance and environmental sustainability indicators,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 79 publications
0
36
0
5
Order By: Relevance
“…Social responsibility and taking care of stakeholders are significant sustainable issues in hotels amid the COVID‐19 and post‐COVID‐19 pandemic (Pelikanova et al, 2021 ). Duric and Topler ( 2021 ) found that hotels implemented the following sustainable practices: waste minimization, waste disposal, emissions minimization, and reduction of energy and water consumption.…”
Section: Review Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Social responsibility and taking care of stakeholders are significant sustainable issues in hotels amid the COVID‐19 and post‐COVID‐19 pandemic (Pelikanova et al, 2021 ). Duric and Topler ( 2021 ) found that hotels implemented the following sustainable practices: waste minimization, waste disposal, emissions minimization, and reduction of energy and water consumption.…”
Section: Review Findingsmentioning
confidence: 99%
“…A critical area for future research is to explore further sustainable practices that are more resilient to being implemented by restaurants because of COVID‐19 (Ocampo et al, 2021 ). In addition, it is recommended to explore sustainable practices in various hotels (Duric & Topler, 2021 ; Salem, Elbaz, et al, 2021 ; Salem, Elkhwesky, & Ramkissoon, 2021 ). It is suggested that future research examine the impact of environmentally sustainable practices on consumers' behavioral intentions in hospitality.…”
Section: Post‐covid‐19 Agenda and Call For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…El concepto de la marca Club Amigo comprende diversos elementos: 1) Instalaciones ubicadas en zonas de playa; 2) Instalaciones de categoría 3 estrellas con modalidad Todo Incluido; 3) Orientada básicamente al segmento familia, aunque accedan otros segmentos como el de parejas, adultos mayores y jóvenes. Todo ello, enmarcado en un ambiente acogedor (Duric & Topler 2021:3) con la presencia de objetos de la cultura nacional, que destacan los valores y manifestaciones artísticas de la localidad donde está ubicada cada instalación.…”
Section: Tabla 1 Perspectiva De Los Clientes Sobre Principales Atribu...unclassified
“…The difficulties in adopting ESG and SDGs concepts also exist among the SMEs operating within the H&T sector. Particularly to the sustainable practice conducted by the international hotels, some studies show mixed results concerning the impact of ESG practice on the hotel's financial performance with regards to its cost efficiency and profitability (see, cf., Duric and Topler, 2021;Pereira, Silva and Dias, 2021). Nonetheless, those studies indicate that a sustainable practice that follows the concept of ESG and SDGs can positively influence the hotels' value-particularly on their financial performance.…”
Section: Introductionmentioning
confidence: 99%